2018
DOI: 10.1016/j.pdpdt.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid photodynamic therapy in refractory vulvar lichen sclerosus et atrophicus: Series of ten cases

Abstract: ALA-PDT is an effective and safe approach for the treatment of VLSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…In a study performed on ten patients with refractory vulvar LS, nine out of ten patients reported improved clinical response and complete disappearance of itching and one patient reported decrease of itching from severe to mild. Side effects were pain, swelling and erythema and were tolerable (107). Another study performed on 102 patients with vulvar LS treated with ALA-PDT weekly for ten weeks found complete and partial response in 87.25% of patients, the greatest response being observed in the reduction of subepithelial ecchymoses and telangiectasia (108).…”
Section: Updates In Pdt For Lichen Sclerosus -A Dermatosis With Potenmentioning
confidence: 96%
“…In a study performed on ten patients with refractory vulvar LS, nine out of ten patients reported improved clinical response and complete disappearance of itching and one patient reported decrease of itching from severe to mild. Side effects were pain, swelling and erythema and were tolerable (107). Another study performed on 102 patients with vulvar LS treated with ALA-PDT weekly for ten weeks found complete and partial response in 87.25% of patients, the greatest response being observed in the reduction of subepithelial ecchymoses and telangiectasia (108).…”
Section: Updates In Pdt For Lichen Sclerosus -A Dermatosis With Potenmentioning
confidence: 96%
“…Photodynamic therapy (PDT) with the use of topical 10% 5-ALA cream (5-aminolaevulinic acid) has been found to be useful in treating VLS [ 32 ]. In a study, after application of freshly prepared 10% 5-ALA cream with a one-cm margin and incubating for three hours, the lesions were irradiated with 100 J/cm 2 633 nm red light at 100 mW/cm 2 [ 33 ]. The same PDT procedure was repeated three times at two-week intervals.…”
Section: Reviewmentioning
confidence: 99%
“…Sixteen studies have described the efficacy of PDT in the resolution of pruritus. The considerable reduction of itching as measured by VAS or VRS scales was reported in eight publications [ 28 , 29 , 31 , 34 , 35 , 38 , 40 , 41 ]. Other studies indicated high therapeutic efficacy of PDT in relieving pruritus, in some cases of a gradual nature with subsequent treatments [ 27 , 30 , 32 , 33 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%